Data Mining: Perception of Customers towards Privacy Invasion - Kumar, D; Ankita, Ankita (International Journal of Computer Sciences and Engineering, 2025)
Abstract - Nowadays ample amount of data including personal data is being collected by government and private sector. This data in turn helps in running countries and their economy effectively and efficiently. In order to achieve this, private as well as government institutions collect clients or consumers data. To be more specific, in retail sector, we can say, the more data they gather, the better will be the results. But, the more personal data which is collected and analyzed, the more individuals are at risk of crimes. One must be aware of privacy invasions and its rules. As coin has two sides, same goes with data mining; it too has positive and negative aspects. Nowadays, technology is advancing and so more of the awareness is required from the customers’ side. In this paper I look at the perception of customers towards privacy invasion with reference to data mining and how Customer tracking technology work in offline Retail Stores.